Postoperative evaluation of transpedicular screws with computed tomography - (:unkn) unknown (My University, 1994)
The accuracy of screw placement was assessed with postoperative computed tomography (CT) scans in 75 consecutive patients treated with transpedicular screw fixation. The pedicular screws (n = 379) were inserted at levels ranging from thoracal (T-8) to sacral (S-2) vertebrae using different systems. Most of the screws (90%) were correctly placed in the pedicle. Ten screws (3%) were inserted medially into the spinal canal. Only 1 screw caused root compression symptoms. Screw misplacement lateral to the pedicle occurred in 18 cases (5%), 9 screws (2%) were inserted superior to the pedicle. No important complications developed that were related to the misplaced screws.
Keywords: Adult; Humans; Middle Aged; Treatment Outcome; Aged; Tomography, X-Ray Computed; Adolescent; Thoracic Vertebrae; Lumbar Vertebrae; Bone Screws; Spinal Diseases; Orthopedics; Sacrum